A comparison of physical characteristics of pine shavings biosecure pine shavings and sunflower hulls as litter material and its influence on broiler performance - Jansen van Rensburg, Christine (University of Pretoria, 2018)
Dissertation (MSc (Agric))--University of Pretoria, 2017.